Efektivitas Mindfulness dalam Menurunkan Burnout pada Mahasiswa Kedokteran - Aziz Alqadri Setiawan; Sulthan Rafi Abyan; Ahmad Fajar Sidik (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Burnout is a psychological condition characterized by emotional exhaustion, depersonalization, and decreased personal achievement, commonly experienced by medical students. Mindfulness, defined as awareness and acceptance of the present moment without judgment, has been increasingly studied as a strategy to reduce burnout. This narrative literature review aims to evaluate the effectiveness of mindfulness interventions in reducing burnout levels among medical students. Articles were collected from PubMed, ScienceDirect, and Google Scholar published between 2020 and 2025. Studies indicate that mindfulness-based programs, such as Mindfulness-Based Stress Reduction (MBSR) and brief online mindfulness training, effectively reduce emotional exhaustion and improve psychological well-being. Mindfulness promotes self-regulation, decreases stress reactivity, and enhances empathy, which are essential for medical students’ mental health. In conclusion, mindfulness interventions show significant potential in alleviating burnout among medical students and should be considered as part of medical education curricula.